Indoor air quality in Portuguese schools: levels and sources of pollutants - Madureira, Joana (2017)
Indoor air quality (IAQ) parameters in 73 primary classrooms in Porto were examined for the purpose of assessing levels of volatile organic compounds (VOCs), aldehydes, particulate matter, ventilation rates and bioaerosols within and between schools, and potential sources. Levels of VOCs, aldehydes, PM2.5 , PM10 , bacteria and fungi, carbon dioxide (CO2 ), carbon monoxide, temperature and relative humidity were measured indoors and outdoors and a walkthrough survey was performed concurrently. Ventilation rates were derived from CO2 and occupancy data. Concentrations of CO2 exceeding 1000 ppm were often encountered, indicating poor ventilation. Most VOCs had low concentrations (median of individual species <5 μg/m(3) ) and were below the respective WHO guidelines. Concentrations of particulate matter and culturable bacteria were frequently higher than guidelines/reference values. The variability of VOCs, aldehydes, bioaerosol concentrations, and CO2 levels between schools exceeded the variability within schools. These findings indicate that IAQ problems may persist in classrooms where pollutant sources exist and classrooms are poorly ventilated; source control strategies (related to building location, occupant behavior, maintenance/cleaning activities) are deemed to be the most reliable for the prevention of adverse health consequences in children in schools.